2022
DOI: 10.3389/fneur.2022.830029
|View full text |Cite
|
Sign up to set email alerts
|

Myelitis: A Common Complication of Tuberculous Meningitis Predicting Poor Outcome

Abstract: BackgroundMyelitis is an important complication in patients with tuberculous meningitis (TBM). However, a paucity of publications exists on the spectrum of neurological and MRI findings of TBM-related myelitis. The risk factors and prognosis of myelitis in patients with TBM are not fully understood. Therefore, this study aims to identify the risk factors, clinicoradiological features, and prognostic impact of myelitis for patients with TBM.MethodsWe conducted a retrospective study in our institution. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…We found that the cervico-dorsal spinal cord was the most commonly involved area in cases of tuberculous myelitis. The findings of cervico-dorsal LETM as a common imaging manifestation of tuberculous myelitis are consistent with other recent studies [24]. Other neuroimaging findings were the presence of spinal meningeal enhancement, CSF loculation, tuberculoma, extra-axial collection, and arachnoiditis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the cervico-dorsal spinal cord was the most commonly involved area in cases of tuberculous myelitis. The findings of cervico-dorsal LETM as a common imaging manifestation of tuberculous myelitis are consistent with other recent studies [24]. Other neuroimaging findings were the presence of spinal meningeal enhancement, CSF loculation, tuberculoma, extra-axial collection, and arachnoiditis.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that tuberculous myelitis may not be an isolated entity; rather, it can be a combination of meningo-myelitis. A similar combination of neuroimaging findings has also been described in other studies [24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Early evidence for TB-M includes lymphocytic pleocytosis and normal or low glucose levels on CSF and a positive IGRA test [4]. Central nervous system infarctions, communicating hydrocephalus and basal meningeal, and spinal cord enhancement on post-contrast are common findings in MRI [3,[5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory myelopathies constitute the most frequently occurring myelopathies and have diverse immune-mediated disease mechanisms associated with them. With a better understanding of the immune process and the discovery of new disease biomarkers, the diagnostic spectrum of this group of myelopathies continues to expand ( table 1-4 52-59 and table 1-5 60-67 ). The mechanisms of immune-mediated disease include demyelinating disease associated with multiple sclerosis, autoimmune myelopathies associated with specific antibodies against neural antigens (eg, NMO, MOG-associated disorders, paraneoplastic disorders), autoimmune myelopathies related to systemic autoimmune or rheumatologic diseases (eg, Sjögren syndrome, systemic lupus erythematous), infection-associated myelopathies, and other inflammatory myelopathies caused by the use of medications that target immune pathways that trigger autoimmune responses against the spinal cord such as immune checkpoint inhibitors used in cancer treatment 68 or tumor necrosis factor inhibitors in the treatment of rheumatologic disorders 69 …”
Section: An Integrative Approach To Diagnosis Of Myelopathymentioning
confidence: 99%